MOLDING MATERIALS USED IN DENTISTRY (PART II) REFRACTORY MOLDING MATERIALS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
In modern dentistry, the technologies of casting metal alloys and molding pressing of ceramic materials are widely used. Molds for casting metal alloys and extrusion of ceramics are made of refractory molding materials. The article presents the classification of types and types of refractory molding materials used, their characteristics, and describes in detail the features of the technological process.